Why are Hispanic and African-American dropout rates so high? - Magnus Lofstrom (Institute for the Study of Labor (IZA), 2007)
The proportion of students who do not graduate from high school is dramatically higher among the two largest minority groups, Hispanics and African-Americans, compared to non-Hispanic whites. In this paper we utilize unique student-level data from the Texas Schools Microdata Panel (TSMP) in an attempt to determine what factors contribute to the higher minority dropout rates. We show that poverty is a key contributor. Lack of English proficiency among Hispanic student is linked to the higher Hispanic dropout probability. Our results also suggest that neighborhood characteristics may be important in explaining the high African-American dropout rates. We also address the issue of the surprisingly low official dropout rates reported by the Texas Education Agency (TEA) and show that the GED program explains some of the discrepancy.
Keywords: I21; 370; Dropout rate; educational attainment; Allgemeinbildende Schule; Abbrecher; Hispano-Amerikaner; Farbige Bevölkerung; Bildungsniveau; Armut; Englisch (Sprache); USA